2018
DOI: 10.1016/j.jclepro.2017.11.241
|View full text |Cite
|
Sign up to set email alerts
|

Review on environmental models in the food chain - Current status and future perspectives

Abstract: Review on environmental models in the food chain-current status and future perspectives, (2017),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 148 publications
1
42
0
Order By: Relevance
“…3 From eco-labelling to multidimensionality in the food sector There are numerous methods and models which have been specifically developed and adapted to the planning, processing activities and control of the food sector, from farm to retail and household. The focus is not only on reducing costs, but also on fostering sustainability and preserving the environment (Akkerman et al, 2010;Manzini-Accorsi, 2013;Battini et al, 2014;Djekic et al, 2018).…”
Section: Defining the Sustainability Information Gapmentioning
confidence: 99%
“…3 From eco-labelling to multidimensionality in the food sector There are numerous methods and models which have been specifically developed and adapted to the planning, processing activities and control of the food sector, from farm to retail and household. The focus is not only on reducing costs, but also on fostering sustainability and preserving the environment (Akkerman et al, 2010;Manzini-Accorsi, 2013;Battini et al, 2014;Djekic et al, 2018).…”
Section: Defining the Sustainability Information Gapmentioning
confidence: 99%
“…Considering that there are a large number of different types of standards and regulations related to hygienic design and due to the redundancy of many requirements, a compact tool for evaluating novel technologies is more than needed [33]. In the future, studies related to comparison of environmental impacts of novel and conventional techniques will need to go in two directions: (i) improving the environmental performance of nonthermal technologies per se, and (ii) comparing environmental aspects of nonthermal and conventional technologies, along with weighting other factors such as quality of the final product or investment costs [2].…”
Section: Future Challenges Of Novel Nonthermal Technologies and Conclmentioning
confidence: 99%
“…Besides the food safety and quality dimensions, these processing technologies have the possibility to shorten treatment time, lower energy consumption, and lower carbon footprint [2].…”
Section: Introductionmentioning
confidence: 99%
“…The results of conceptual as well as empirical studies regarding the effectiveness of codes of conduct are mixed (see [24]). Recent studies have confirmed that codes of conduct based on external standards have positive impacts on social and environmental performance [25][26][27][28]. However, some studies address signaling effects as the main motive for the establishment of codes of conduct [19,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies provide evidence that the application of an environmental management system based on ISO 14001 requirements positively affects companies' environmental performance [25,[42][43][44]. However, ISO 14001 is a generic standard related to environmental management and does not define specific level of environmental performance "but focuses on requiring organizations to comply with the specified characteristics of the system with such compliance expected to assist organizations in achieving their own environmental objectives" [45].…”
Section: Introductionmentioning
confidence: 99%